A study of the factors that influence employee performance in Renaissance Kota Bharu Hotel / Siti Nurul Akma Che Mat - Che Mat, Siti Nurul Akma (2015)
This study is designed to determine the relationship between reward systems, leadership, working environment and performance management system towards employee performance. Employee performance is important because it will contribute to the success of the hotel. The hotel need a good employee to interact with the guest so that they will come back to hotel and brings a good memory.Reward system also can influence the employee's performance towards work. Reward can be a motivator for the employee in doing the work done on time. It also can create employee loyalty towards the hotel. Leadership is able to facilitate cooperation within an organization among employer and employees. Working environment also is tested because employees need a good workplace to do the job. In term of performance management system, it is the evaluation tools used by the hotel that equivalent with the employee performance. This study is conducted in Renaissance Kota Bharu Hotel and the respondents are all workers in Renaissance Kota Bharu Kelantan. The total population as at the time of the study is found to be 250 and the suitable sample size is 152. Convenience sampling technique is used in this study. Data was collected over duration of seven weeks from 15 March 2015 to 30 April 2015. The finding shows that reward system (r=0.843, p<0.01) and working environment (r=0.707, p<0.01), were significantly and positively correlated with employee performance. Meanwhile, leadership (r=-0.721, p<0.01) and performance management system (r=-0.199, p<0.05), were significantly and negatively correlated with employee performance. Thus, this study will contribute to the employee performance in hotel industry.